A Comprehensive Analysis of Mortality due to COVID-19 in Long-Term Care - Hothi, Harneet (My University, 2022)
The long-term care (LTC) sector in Canada has experienced high numbers of COVID-19 deaths. However, there is a paucity of data on the impact of COVID-19 in LTC by different socio- demographic variables and in LTC homes within different regions. Additionally, the question remains as to how exactly and by how much the pandemic has impacted mortality in LTC in comparison to previous years’ mortality. Ranges for expected mortality by sex, province, and age, for the 2020-21 fiscal year were determined by creating forecasts and confidence intervals based on mortality trends in the preceding four fiscal years. These ranges were then compared to the actual mortality data in 2020-21. Comparisons between expected ranges and actual data were also conducted for the number of active residents, admissions, and discharges in LTC by sex, province, and age. Further, mortality ratios were created and studied by sex, province, age, and health region/authority/local health integration network. Overall, the number of deaths in LTC in Canada increased beyond the expected ranges in quarter one and three of 2020-21, and the patterns in death ratios were similar. Increases were exceptional in comparison to the peaks in deaths in previous years for specific variables, but not all variables. Most commonly, the number of active residents and admissions decreased in 2020-21 and the number of discharges from LTC did not change in quarter one and three and decreased in quarter two and four. However, importantly, these trends also varied across variables. This was the first study to comprehensively examine mortality due to COVID-19 in LTC overall, and by multiple socio- demographic variables while elucidating the complexity in the study of mortality in LTC. Further research is required to concretely understand mortality in LTC by different variables and regions.
Mortality due to COVID-19 in Canadian Long-Term Care
Keywords: Long-Term Care; COVID-19 Mortality